A MONOGRAPH OF THE GENUS SCHOUTENIA*) Korth. (Tiliaceae) - ROEKMOWATI ROEKMOWATI; HARTONO HARTONO (BRIN Publishing (Penerbit BRIN), 1965)
The genus consists of 8 species in Siam, Indochina, the Malay Peninsula, Sumatra, Borneo, Java, and the Lesser Sunda Islands. It is here divided into 2 subgenera, the monotypic Schoutevia with S. cvata Korth. and Chartacalyx with S. accrescens (Mast.) Curtis as type species. Chartacalyx is divided into 2 sections, Chartacalyx and A disci flora with S. kuiistleri King as type spscies.Three species, S. curtisii, corneri, and kostermansii are considered new. S. hypoleuca Pierre is reduced to synonymy of S. ovata Korth.S. peregrines Craib is reduced to a subspecies of S. glomerata King.The varieties of S. accrescens (Mast.) Curtis are deleted. The species is divided into 3 subspecies: accrescens, stellata, and borneensis. A forma lepidota is reeognized for subspecies accrescens.S. buurmanii K. et V. and S. kunstleri King- are considered to be different species.